Mekanisme Pengangkatan Dan Pemberhentian Perangkat Desa: Sebuah Tinjauan Hukum - Desi Sommaliagustina (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
Indonesia as a legal state, the implementation of governments is based on the principle of law supremacy, thus e ach deed by the government must be in line with the existing law. This condition gave birth to an antithesis that the government's deeds outside of it can not be authorized, beyond authority, or arbitrary. Problems, in Lord acton terms, known toes Power texs to Corrupt; Absolute Power Corruptsare absoluteely so that without the restriction of power then the direction destined by the government is only a particular interest and certain groups alone. Different conditions with the Government that embrace the system of absolute monarchy, with the inflammatory authority of the unlimited, because the king is the law it self.